Advances in Human Factors, Sustainable Urban Planning and Infrastructure Proceedings of the AHFE 2018 International Conference on Human Factors, Sustainable Urban Planning and Infrastructure, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA - Charytonowicz, Jerzy; Falcão, Christianne; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book discusses human factors research directed towards realizing and assessing sustainability in the built environment. It reports on advanced engineering methods for sustainable infrastructure design, as well as on assessments of the efficient methods and the social, environmental, and economic impact of various designs and projects. The book covers a range of topics, including the use of recycled materials in architecture, ergonomics in buildings and public design, sustainable design for smart cities, design for the aging population, industrial design, human scale in architecture, and many more. Based on the AHFE 2018 International Conference on Human Factors, Sustainable Urban Planning and Infrastructure, held on July 21-25, 2018, in Orlando, Florida, USA, it offers various perspectives on sustainability and ergonomics. As such, it is a valuable reference resource for designers, urban engineers, architects, infrastructure professionals, public infrastructure owners, policy makers, government engineers and planners, as well as operations managers and academics active in urban and infrastructure research.
Part I: Ergonomics in Material and Environment Design -- Urban green spaces: An element of a city's balance between the built and natural environments -- Open-air work zones for students at the faculty of architecture depicted on the basis of pilot student projects -- The campus space in research and student projects.
Keywords: Buildings -- Design and construction; Sustainable architecture; Urban economics; Computational intelligence; User interfaces (Computer systems).; Human-computer interaction; Building Construction and Design; Sustainable Architecture/Green Buildings; Urban Economics; Computational Intelligence; User Interfaces and Human Computer Interaction